Answer:3
Step-by-step explanation:
-9x+4=-8-5x
-4x+4=-8
-4x=-12
x=3
Answer:
Step-by-step explanation:
Add 5x so -9x+5x becomes -4x+4=-8 then subtract -4 and then -4+-8 becomes -12 and then solve for x which is -12/-4 which is 3.
Step-by-step explanation:
The options are not to clear, nevertheless let us model the expression for the cost.
Let y be the total cost
And x be the number of miles
Given that the fixed rate is $8 and $4 for each extra mile traveled
The total cost is
y=8+4x
For a 5 mile journey the cost is
y=8+4(5)
y=8+20
y=28
$28
B. 11 and 12
C. 12 and 13
D. 133 and 135
but the question is not clear
f(x) = 4x − 3
f(x) = 4x + 3
f(x) = 4(x + 3)
Answer:
f(x) = 4^x -3
Step-by-step explanation:
All of the listed functions are linear functions with a constant slope of 4. None of them goes through the point (0, -2).
__
So, we assume that there is a missing exponentiation operator, and that these are supposed to be exponential functions. If the horizontal asymptote is -3, then there is only one answer choice that makes any sense:
f(x) = 4^x -3
_____
The minimum value of 4^z for any z will be near zero. In order to make it be near -3, 3 must be subtracted from the exponential term.
the answer is 11
11x3= 33
33-12=21